Behavioral intention to green consumption: A perspective of Muslim consumers in Bangladesh: Behavioral intention to green consumption (IIUC Business Review, 2026)
Green consumption refers to environmentally friendly practices involving biodegradable, energy-efficient, reusable, and organic products. This study examines how behavioral intentions influence green consumption among Muslim consumers in Bangladesh. Behavioral intention is treated as the independent variable and actual green consumption as the dependent variable. Data were collected from 255 respondents through a mall-intercept survey, yielding a 63% valid response rate. Path analysis using SMART-PLS shows a positive relationship between intention and behavior, with a path coefficient of 0.138, t-value of 2.941 (p < 0.01), and p-value of 0.003, indicating that stronger intention significantly predicts green consumption. Muslim consumers demonstrated a favorable attitude toward green behavior and a strong intention to purchase sustainable products. The findings highlight the critical role of behavioral intention in explaining green consumption. Methodologically, the application of SMART-PLS offers a robust framework for studying intention–behavior links. Practically, marketers can leverage these insights to design strategies aligning green products with Muslim consumers’ values, thereby boosting demand for sustainable offerings.IIUC Business Review, Vol.-12, Issue-1, December 2023, pp. 9-24